Ecuadorian Public High School Teachers Perceptions on Technological Resources used by teachers in their EFL Classrooms during the Covid19 Pandemic - Maza Campoverde, Nelly Carmita (2021)
Resumen:The study intended to analyze the technological resources employed by teachers in their EFL classrooms during the Covid-19 pandemic in Ecuadorian public schools. In order to reach that objective, a qualitative and quantitative approach was applied, by means of a survey and interviews, using a teacher questionnaire given to ten EFL public high school teachers from seven Ecuadorian towns located in two provinces. Both female and male, of different ages and experience in teaching participated as sample. In order to do the analysis, three dimensions were considered; the type of technological resources and frequency of use, the self-assessed competency in employing said resources and the teacher’s attitudes and perceptions towards them. After the analysis, the study concluded that all teachers use technological resources in their EFL classrooms, that the overall majority consider to have the necessary skills and knowledge to solve technological problems that arise in class and that the perception and attitudes of the teachers towards using those technological resources are generally positive. Further investigation, especially related to teachers’ perceptions towards technology use and increasing competency is recommended.